Effect of forced convection roasting on physicochemical and antioxidant properties of whole grain maize (Zea mays L.) and optimisation of roasting conditions - Bala, Shuaibu Mallam (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD Food Sc)--Stellenbosch University, 2016.